2007
DOI: 10.1007/s12020-007-0024-9
|View full text |Cite
|
Sign up to set email alerts
|

Two novel genotypes of the thiazide-sensitive Na-Cl cotransporter (SLC12A3) gene in patients with Gitelman’s syndrome

Abstract: Gitelman's syndrome is an autosomal recessive disorder marked by salt wasting and hypokalaemia resulting from loss-of-function mutations in the SLC12A3 gene that codes for the thiazide-sensitive Na-Cl cotransporter. Gitelman's syndrome is usually distinguished from Bartter's syndrome by the presence of both hypomagnesaemia and hypocalciuria. Although recent advances in molecular genetics may make it possible to both diagnose and differentiate these diseases, the phenotypes sometimes overlap. Here we report two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…To our knowledge, it is the first report of a GS patient with hypothyroidism. Recently, it was reported that two GS patients were affected with Hashimoto's disease and Graves' disease, respectively 34 . However, it is not clear whether there is a specific correlation between GS and thyroid diseases.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, it is the first report of a GS patient with hypothyroidism. Recently, it was reported that two GS patients were affected with Hashimoto's disease and Graves' disease, respectively 34 . However, it is not clear whether there is a specific correlation between GS and thyroid diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Participants with cancer or autoimmune disease, including antiphospholipid antibody syndrome, were also excluded. Informed consent was obtained from each subject according to a protocol approved by the Human Studies Committee of Nihon University [17].…”
Section: Subjectsmentioning
confidence: 99%
“…The Clinical Laboratory Department of Nihon University Hospital used standard laboratory methods to measure the serum total cholesterol, HDL cholesterol, creatinine and uric acid concentrations, fasting blood sugar, and HbA1c in blood [30].…”
Section: Biochemical Analysismentioning
confidence: 99%